A modified aluminate cement and its preparation method and application
By combining aluminate cement with fluorogypsum and KH2PO4, a composite cementitious material with fibrous ettringite was generated, which solved the problem of unstable strength of calcium aluminate cement in the later stage, and achieved early, strong, fast and hard grouting material performance.
Patent Information
- Application Number
- CN202311291869.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-10-08
AI Technical Summary
Calcium aluminate cement has unstable strength in the later stage due to the unstable properties of the hydrated products and is relatively high in production costs, making it difficult to use as a grouting material.
By combining aluminate cement with fluorogypsum and KH2PO4, its settling time and compressive strength are regulated to produce a composite gelling material with fibrous ettringite.
The initial setting and final setting time of calcium aluminate cement is significantly shortened, and the compressive strength of 3d and 28d is improved, solving the problem of later strength instability.
Smart Images

Figure CN117486513B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to modified aluminate cement and a preparation method and application thereof. Background Art
[0002] Aluminate cement is a hydraulic cementitious material made from bauxite and limestone, which is calcined to produce a clinker with calcium aluminate as the main component and an alumina content of about 50%, and then ground into a material. The main minerals of aluminate cement are monocalcium aluminate (CaO·Al2O3, abbreviated as CA) and other aluminates, as well as a small amount of dicalcium silicate (2CaO·SiO2, abbreviated as CA2). Compared with silicate cement, it is a low-carbon cement. However, since calcium aluminate cement has the characteristic that its compressive strength changes unstably with temperature and humidity, it has been prohibited from being used as a cementitious material for structural elements. The instability of the later strength of calcium aluminate cement is mainly caused by the phase transformation caused by the unstable characteristics of the hydration products. The main minerals of calcium aluminate cement are CA, CA2, C 12 A7, after hydration, will be unstable compound CAH 10 , C2AH8 eventually transforms into stable compounds C3AH6 and Al(OH)3, among which CAH 10 and C2AH8 are the reasons for the high early strength of CAC. During the crystal transformation process, the volume decreases and the porosity of the hardened body increases, which leads to the instability of the later strength of aluminate cement. In addition, the production cost of aluminate cement used as grouting material is high and the later strength is unstable.
[0003] Calcium aluminate cement is a common aluminate cement. The hydration products of calcium aluminate cement have always been the focus of research. In this regard, some scholars have explored the influence of hydration products by adding chemical admixtures or physical means: DimasAlan Strauss Rambo et al. studied the effect of adding clinker aggregate to calcium aluminate cement on hydration products. The results showed that hydration products can form a dense layer on the surface of the structure, so that it has better bonding performance in the interface area, thereby improving the mechanical properties. T.Manninger added phosphoric acid to calcium aluminate cement and found that phosphoric acid can significantly change the calcium ion (Ca 2+ ) and aluminum ions (Al 3+ ) concentration, providing a reaction buffer period, thereby affecting the hydration reaction process and the formation process of the hydrate phase. On the other hand, some researchers have improved the later strength by generating other hydration products: L. Fernández-Carrasco et al. conducted supercritical carbonation curing on calcium aluminate cement specimens. The results showed that the main products after supercritical carbonation curing were calcium carbonate and aluminum hydroxide. HMSon a et al. added nano-silica to calcium aluminate cement to delay the metastable hydration product CAH10 and C2AH8 to the stable phase C3AH6, and by generating (C2ASH8) to maintain the long-term strength of aluminate cement.
[0004] Grouting materials can be used to fill and consolidate in stratum fissures and pores, and they are the key to achieving water blocking or reinforcement. In some projects, grouting materials are required to have the characteristics of early strength and fast hardening, such as water blocking and rapid repair projects. In order to prepare early strength and fast hardening grouting materials, some are based on silicate cement-based grouting materials, by adding early strength agents or nanomaterials, and some use polymer grouting materials such as polyurethane, but there are disadvantages such as high cost. In contrast, pure aluminate cement grouting materials are rarely used due to their unstable characteristics of late strength development. On the contrary, it is more common to use aluminate cement in combination with other cements as grouting materials, such as silicate cement and sulphoaluminate cement.
[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0006] In view of the problem that the strength development of existing calcium aluminate cement is unstable due to phase transformation, the purpose of the present invention is to provide a modified aluminate cement and a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The invention provides a modified aluminate cement. The raw materials thereof comprise 90% aluminate cement, 10% fluorgypsum and 0.1-0.4% KH2PO4 of the total weight of the raw materials in terms of weight percentage.
[0009] Preferably, the raw material composition includes, by mass percentage, 90% aluminate cement and 10% fluorgypsum, and 0.2% KH2PO4 based on the total mass of the above raw materials.
[0010] Preferably, the aluminate cement is calcium aluminate cement.
[0011] Preferably, the chemical composition of the calcium aluminate cement comprises, by mass percentage, Na2O 0-1%, MgO 0-2%, Al2O3 50-60%, SiO2 5-8%, CaO 25-35%, Fe2O3 2-4% and others 0-4%.
[0012] Preferably, the main particle size of the calcium aluminate cement is: D 10 2-10μm, D 50 35-55μm, D 90 100-200μm.
[0013] Preferably, the chemical composition of the fluorgypsum includes, by mass percentage: SO3 55-58%, CaO 40-42.5%, Al2O3 0-0.5%, SiO2 0-0.5%, MgO 0-0.05%, Fe2O30-0.5%, K2O 0-0.05%, F - 0-1.5% and others 0-0.2%.
[0014] Preferably, the main particle size of the fluorgypsum is: D 10 0-2μm, D 50 2-5μm, D 90 30-100μm.
[0015] Preferably, the KH2PO4 is analytically pure.
[0016] The present invention provides a method for preparing the modified aluminate cement, comprising the following steps:
[0017] (1) Weigh aluminate cement, fluorgypsum, and KH2PO4 according to the raw material ratio and set aside;
[0018] (2) Mix aluminate cement, fluorgypsum and KH2PO4, and stir at a speed of 120-160 r / min for 120-180 s to obtain.
[0019] The invention provides application of the modified aluminate cement in grouting materials.
[0020] Beneficial effects:
[0021] Aluminate cement has the characteristics of fast hardening and early strength. By compounding it with fluorgypsum and the like and adding chemical admixtures, a composite cementitious material with better performance can be prepared. The present invention aims at the hydration products and hydration characteristics of existing calcium aluminate cement, compounds it with fluorgypsum, and modifies it by adding potassium dihydrogen to obtain a new composite cementitious material.
[0022] The present invention uses fluorgypsum and KH2PO4 to regulate the setting time and compressive strength of aluminate cement. The results show that 10wt% fluorgypsum promotes the formation of calcium sulfonate, and 0.2wt% KH2PO4 further optimizes the formation of calcium sulfonate. The addition of both optimizes the hydration products and pore structure of calcium aluminate cement, especially KH2PO4 changes the morphology of calcium sulfonate from needle-like to fibrous. Correspondingly, at 10wt% fluorgypsum and 0.2wt% KH2PO4, the initial setting time and final setting time are shortened by 39% and 38% respectively; the 3d and 28d compressive strengths are increased by 76% and 228.80% respectively. This has a good reference role in the performance regulation of aluminate cement-based grouting materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0024] Figure 1 It is the XRD diffraction pattern and particle size distribution diagram of the calcium aluminate cement of the present invention.
[0025] Wherein, C1 is comparative example 1, C2 is comparative example 2, D1 is embodiment 1, D2 is embodiment 2, D3 is embodiment 3, D4 is embodiment 4, and the following Figure 2-12 same.
[0026] Figure 2 The XRD diffraction pattern and particle size distribution diagram of the fluorgypsum of the present invention are shown in FIG.
[0027] Figure 3 It is the setting time of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples.
[0028] Figure 4 It is the compressive strength of the calcium aluminate cement obtained in the comparative example of the present invention.
[0029] Figure 5 It is the compressive strength of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples.
[0030] Figure 6 It is the pH value of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples.
[0031] Figure 7 The XRD diagrams of the calcium aluminate cements obtained in the examples and comparative examples of the present invention are shown in FIG.
[0032] Figure 8 TG-DTG diagram of calcium aluminate cement obtained in Examples of the present invention and Comparative Examples.
[0033] Fig. 9 The SEM images of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples after hardening for 3d and 28d are shown in FIG.
[0034] Fig.10 2 is the T2 distribution diagram of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples.
[0035] Fig.11 The porosity of the calcium aluminate cement obtained in the examples of the present invention and the comparative examples.
[0036] Fig.12 The calcium aluminate cement samples obtained in the examples and comparative examples of the present invention are<t2>Data are plotted as a function of hydration time.
[0037] Fig.13 Schematic diagram of the hydration mechanism of the modified calcium aluminate cement of the present invention.
[0038] Among them, (a) no KH2PO4 and fluorgypsum are added; (b) only fluorgypsum is added; (c) fluorgypsum and KH2PO4 are added. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0040] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0041] In view of the existing problems, the present invention provides a modified aluminate cement. The raw material composition comprises 90% aluminate cement and 10% fluorgypsum by mass, and 0.1-0.4% (for example, 0.1%, 0.2%, 0.3% or 0.4%) KH2PO4 of the total mass of the above raw materials.
[0042] In a preferred embodiment of the present invention, the raw material composition includes, by mass percentage, 90% aluminate cement and 10% fluorspar, and 0.2% KH2PO4 of the total mass of the above raw materials.
[0043] In a preferred embodiment of the present invention, the aluminate cement is calcium aluminate cement.
[0044] In a preferred embodiment of the present invention, the chemical composition of the calcium aluminate cement includes, by mass percentage: Na2O 0-1%, MgO 0-2%, Al2O3 50-60%, SiO2 5-8%, CaO 25-35%, Fe2O3 2-4% and other 0-4%.
[0045] In a preferred embodiment of the present invention, the chemical composition of the calcium aluminate cement includes, by mass percentage, 0.75% Na2O, 1.73% MgO, 54.13% Al2O3, 6.25% SiO2, 31.24% CaO, 2.13% Fe2O3 and 3.77% others.
[0046] In a preferred embodiment of the present invention, the main particle size of the calcium aluminate cement is: D 10 2-10 μm (e.g., 2 μm, 4 μm, 8 μm or 10 μm), D 50 35-55 μm (e.g., 35 μm, 40 μm, 44 μm, 50 μm or 55 μm), D 90 100-200 μm (e.g., 100 μm, 120 μm, 160 μm, 180 μm or 200 μm).
[0047] In a preferred embodiment of the present invention, the chemical composition of the fluorgypsum includes, by mass percentage: SO3 55-58%, CaO 40-42.5%, Al2O3 0-0.5%, SiO2 0-0.5%, MgO 0-0.05%, Fe2O30-0.5%, K2O 0-0.05%, F - 0-1.5% and others 0-0.2%.
[0048] In a preferred embodiment of the present invention, the chemical composition of the fluorgypsum includes, by mass percentage: SO3 56.87%, CaO 42.21%, Al2O3 0.12%, SiO2 0.10%, MgO 0.03%, Fe2O3 0.13%, K2O 0.02%, F - 0.40% and other 0.12%.
[0049] In a preferred embodiment of the present invention, the main particle size of the fluorgypsum is: D 10 0-2 μm (e.g., 0.2 μm, 0.6 μm, 1.0 μm or 2.0 μm), D 50 2-5 μm (e.g., 2 μm, 3 μm, 4 μm or 5 μm), D 90 30-100 μm (e.g., 30 μm, 50 μm, 60 μm, 80 μm or 100 μm).
[0050] In a preferred embodiment of the present invention, the KH2PO4 is analytically pure.
[0051] The present invention provides a method for preparing modified aluminate cement, comprising the following steps:
[0052] (1) Weigh aluminate cement, fluorgypsum, and KH2PO4 according to the raw material ratio and set aside;
[0053] (2) Aluminate cement, fluorgypsum and KH2PO4 are mixed, and stirred at a speed of 120-160 r / min (for example, 120 r / min, 130 r / min, 140 r / min, 150 r / min or 160 r / min) for 120-180 s (for example, 120 s, 140 s, 160 s or 180 s) to obtain.
[0054] The invention provides application of modified aluminate cement in grouting materials.
[0055] The modified aluminate cement of the present invention and its preparation method and application are described in detail below through specific embodiments.
[0056] The raw materials used in the following examples are:
[0057] The chemical composition of calcium aluminate cement is shown in Table 1. Figure 1 is the XRD diffraction pattern and particle size distribution diagram of calcium aluminate cement. Figure 1 (a) It can be seen that the main minerals are CA, CA2, C2AS and C 12 A7, its particle size distribution is shown in Figure 1 (b), where the main particle size of calcium aluminate cement is: D 10 4.48μm, D 50 43.90 μm, D 90 178μm; the chemical composition of fluorgypsum is shown in Table 2. Figure 2 is the XRD diffraction pattern and particle size distribution diagram of fluorgypsum, Figure 2 (a) It can be seen that the main mineral component is CaSO4, with an effective content of 96.07wt%, a pH of 3.42, and a particle size distribution of Figure 2 (b), where the main particle size of fluorgypsum is: D 10 0.64μm, D 50 3.97μm, D 90 is 59.6μm; KH2PO4 is an analytically pure reagent with an effective content ≥99.5wt%; and the mixing water is laboratory tap water.
[0058] Table 1 Main chemical composition of calcium aluminate cement (wt%)
[0059] <![CDATA[Na2O]]> MgO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> CaO <![CDATA[Fe2O3]]> 0.75 1.73 54.13 6.25 31.24 2.13
[0060] Table 2 Main chemical composition of fluorgypsum (wt%)
[0061] <![CDATA[SO3]]> CaO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> <![CDATA[F - ]]> 56.87 42.21 0.12 0.10 0.03 0.13 0.02 0.40
[0062] Example 1
[0063] This embodiment provides a modified aluminate cement, wherein the raw material composition includes, by weight percentage, 90% calcium aluminate cement and 10% fluorgypsum, and 0.1% KH2PO4 of the total weight of the above raw materials.
[0064] The preparation method of the modified aluminate cement comprises the following steps: mixing calcium aluminate cement, fluorgypsum and KH2PO4 according to the raw material ratio, and stirring at a speed of 140 r / min for 120 seconds to obtain the modified aluminate cement.
[0065] Example 2
[0066] This embodiment provides a modified aluminate cement, wherein the raw material composition includes, by weight percentage, 90% calcium aluminate cement and 10% fluorgypsum, and 0.2% KH2PO4 of the total weight of the above raw materials.
[0067] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0068] Example 3
[0069] This embodiment provides a modified aluminate cement, wherein the raw material composition includes, by mass percentage, 90% calcium aluminate cement and 10% fluorgypsum, and 0.3% KH2PO4 of the total mass of the above raw materials.
[0070] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0071] Example 4
[0072] This embodiment provides a modified aluminate cement, wherein the raw material composition includes, by weight percentage, 90% calcium aluminate cement and 10% fluorgypsum, and 0.4% KH2PO4 of the total weight of the above raw materials.
[0073] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0074] Comparative Example 1
[0075] This comparative example provides an aluminate cement, and the raw material composition comprises 100% calcium aluminate cement by mass percentage.
[0076] Comparative Example 2
[0077] This comparative example provides a modified aluminate cement, wherein the raw material composition comprises 90% of calcium aluminate cement and 10% of fluorgypsum by mass percentage.
[0078] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0079] Comparative Example 3
[0080] This comparative example provides a modified aluminate cement, wherein the raw material composition comprises 80% of calcium aluminate cement and 20% of fluorgypsum by mass percentage.
[0081] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0082] Comparative Example 4
[0083] This comparative example provides a modified aluminate cement, wherein the raw material composition comprises 70% of calcium aluminate cement and 30% of fluorgypsum by mass percentage.
[0084] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0085] Comparative Example 5
[0086] This comparative example provides a modified aluminate cement, wherein the raw material composition comprises 60% of calcium aluminate cement and 40% of fluorgypsum by mass percentage.
[0087] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0088] Comparative Example 6
[0089] This comparative example provides a modified aluminate cement, wherein the raw material composition comprises 50% of calcium aluminate cement and 50% of fluorgypsum by mass percentage.
[0090] The preparation method of the modified aluminate cement is the same as that of Example 1.
[0091] Application Example 1
[0092] Take the aluminate cement obtained in the above examples and comparative examples, add water (water-cement ratio is 0.4) and stir, first stir at a speed of 140 r / min for 120 s, stop for 15 s, and then stir at a speed of 285 r / min for 120 s, and measure the relevant properties.
[0093] (1) Setting time: The setting time is tested in accordance with the Chinese standard “Test Method for Water Consistency, Setting Time and Stability of Cement of Standard Consistency” (GB / T 1346-2011).
[0094] The effect of fluorgypsum and KH2PO4 on the setting time of calcium aluminate cement is shown in Figure 3 .Depend on Figure 3 It can be seen that the initial setting and final setting time of C2 (Comparative Example 2) are slightly longer than those of C1 (Comparative Example 1), which may be due to the addition of 10wt% fluorgypsum, which promotes the formation of calcium sulfonite, thereby producing a retarding effect. With the increase of the KH2PO4 dosage, the setting time is first shortened and then prolonged. When the dosage is 0.2%, that is, D2 (Example 2), the setting time of the slurry is the shortest, and the initial setting time and final setting time are 264min and 308min, respectively, which are shortened by 171min and 187min respectively compared with C1, and shortened by 196min and 207min respectively compared with C2, indicating that the 0.2% dosage of KH2PO4 has a certain promoting effect on the hydration of the composite system of calcium aluminate cement and fluorgypsum; and when the dosage is 0.4% (Example 4), the initial setting and final setting times are extended to 901min and 1021min respectively, which indicates that too much KH2PO4 has an inhibitory effect on the early hydration of the composite cementitious material system.
[0095] (2) Compressive strength: Using specimens with dimensions of 40 mm × 40 mm × 40 mm, the compressive strength at 3 days and 28 days was tested in accordance with the Chinese standard “Test method for strength of cement mortar (ISO method)” (GB / T 17671-2021).
[0096] The effect of fluorinated gypsum on the 3d and 28d compressive strength of calcium aluminate cement is shown in Figure 4 .Depend on Figure 4 It can be seen that as the fluorinated gypsum substitution amount increases from 0% to 50%, the 3d and 28d compressive strengths first increase and then decrease. When the addition amount is 10% (Comparative Example 2), the 3d and 28d compressive strengths are the largest.
[0097] The effects of fluorinated gypsum and KH2PO4 on the 3d and 28d compressive strength of calcium aluminate cement are shown in Figure 5 .Depend on Figure 5 It can be seen that after adding fluorgypsum, the 3d and 28d compressive strengths are significantly increased. This is because fluorgypsum promotes the formation of calcium sulfonate. The reaction mechanism is shown in the following formula (1-2); with the increase of the KH2PO4 dosage, the compressive strength shows a trend of first increasing and then decreasing. When the dosage is 0.2% (Example 2), the compressive strength is the largest, and the 3d and 28d are 26.4MPa and 60.5MPa, respectively, which are 76% and 228% higher than C1 (Comparative Example 1), and 10% and 30% higher than C2 (Comparative Example 2). It can be seen from the influence rule that the more KH2PO4 is added, the better. It is best when the dosage is 0.2%. This may be because 0.2% of KH2PO4 promotes the early formation of calcium sulfonate, but too much dosage may have an adverse effect on the formation of calcium sulfonate, which is unfavorable to the setting time and compressive strength.
[0098] In order to explore the effect of KH2PO4 on the formation of calcium sulfate in the system, the effect of KH2PO4 on the pH value of the system was tested (see Figure 6 ),Depend on Figure 6 It can be seen that as the amount of KH2PO4 increases, the pH of the system gradually decreases, that is, the acidity becomes stronger and stronger, which is conducive to the dissolution of fluorgypsum at the beginning, as shown in the following formula (3), thereby promoting the formation of ettringite. However, as the acidity of the system increases, it has an adverse effect on the formation of ettringite.
[0099] 3CA+3CaSO4+38H2O→C3A·3CaSO4·32H2O+2AH3............(1)
[0100] 3CA2+3CaSO4+47H2O→C3A·3CaSO4·32H2O+5AH3......(2)
[0101]
[0102] (3) Microscopic test: The samples at 3d and 28d were immersed in ethanol for 72h to terminate hydration. During the test, the samples were placed in a vacuum drying oven at 40°C for 48h.
[0103] 1) XRD: An X-ray diffractometer of model SmartLab (9 kW) with a maximum output power of 9 kW, a scanning range of 5° to 75°, and a scanning rate of 5° / min was used.
[0104] Figure 7 The XRD patterns of calcium aluminate cement after hydration for 3d and 28d are shown respectively. Figure 7 It can be seen that the peaks of XRD are mainly the hydration product CAH 10 , C2AH8, C3AH6, AH3, AFt, and unhydrated CA, CA2, C2AS, and C 12 A7. By comparison, it can be found that both 3d and 28d have peaks of ettringite (AFt) when doped with fluorgypsum; when 0.2wt% KH2PO4 is added (Example 2), the diffraction peaks of ettringite at 2θ≈9° and 16° are stronger, which indicates that 0.2% KH2PO4 further promotes the formation of AFt. In addition, compared with 3d, CAH 10 , and the C2AH8 diffraction peaks both become stronger.
[0105] 2) Thermogravimetry: Thermogravimetric test was performed using a HCT-3 microcomputer differential thermal balance with a heating range of 25 to 1000°C and a heating rate of 10°C / min.
[0106] The TG-DTG curves of the effects of fluorgypsum and KH2PO4 on the hydration products of calcium aluminate cement at 3d and 28d are shown in Figure 8 The weight loss rate is shown in Table 3. Figure 8 It can be seen that the main weight loss peaks include CAH at 70-170℃ 10 and AFt, C3AH6 and Al(OH)3 at 230-300℃. From Table 3, we can see that at 3d, CAH 10 The order of the amount of fluorinated gypsum and AFt generated from high to low is: D2>C2>C1; the order of the amount of C3AH6 and Al(OH)3 generated from high to low is: C1>C2>D2, which shows that the addition of fluorinated gypsum and KH2PO4 optimizes the generation of hydration products, especially promotes the generation of CAH 10 and AFt. At 28 days, the influence of the two on the hydration products is consistent with that at 3 days. At 3 days and 28 days, (C3AH6+Al(OH)3) / (CAH 10 The order of the ratio of hydrated phase (A) to hydrated phase (B) is C1>C2>D2, i.e., D2 has the smallest compressive strength, while D2 has the highest compressive strength at the two ages, indicating that it has a certain correlation with the changes in the composition of hydration products.
[0107] Table 3 Effect of fluorgypsum and KH2PO4 on weight loss of calcium aluminate cement hydration products
[0108]
[0109] 3) SEM: The morphology of the samples was examined using a Merlin Compact scanning electron microscope (SEM) from Carl Zeiss NTS GmbH, Germany.
[0110] At 3d and 28d, the SEM images of the effects of fluorgypsum and KH2PO4 on the morphology of calcium aluminate cement hydration products are shown in Fig. 9 .from Fig. 9 It can be seen that the main hydration products of C1 (Comparative Example 1) are CAH 10 , C2AH8, C3AH6 and AH3, C2 (Comparative Example 2) and D2 (Example 2) due to the addition of fluorgypsum, in addition to the above hydration products, the morphology of AFt can also be seen. When only fluorgypsum is added, the morphology of ettringite is short needle columnar, while after adding KH2PO4 (Example 2), the morphology of ettringite is fibrous and overlapped with each other, which shows that fluorgypsum promotes the formation of ettringite, and KH2PO4 further promotes the formation of ettringite and changes its morphology.
[0111] 4) Low-field NMR: The test was performed using a low-field NMR instrument (Suzhou Niumag Analytical Instrument Co., Ltd., China) with a model number of MesoMR12-060V, with an operating frequency of 12 MHz. During the test, the temperature of the magnet and probe was maintained at 32 ± 0.01 °C. The Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence was used to obtain the T2 relaxation time distribution, and the transverse relaxation time (T2) measurement range was (0.001-10000) ms. After the calcium aluminate cement slurry was prepared at a water-cement ratio of 0.40, 15 g of the sample was quickly taken and placed in a glass bottle (inner diameter 22 mm, height 50 mm), and immediately sealed with a sealing film (parafilm) to prevent water evaporation. The first test started when the raw material came into contact with water (0 h), and then the T2 relaxation intensities of the samples were tested at 0.5, 1 h, 3 h, 6 h, 12 h, 24 h, 72 h, 168 h, 336 h, and 672 h of hydration.
[0112] a.T2 spectrum
[0113] Fig.10 The T2 distribution diagram of the effect of fluorgypsum and KH2PO4 on calcium aluminate cement at different ages (0h, 0.5h, 1h, 3h, 6h, 72h, 168h, 336h, 672h) is shown. The reduction in the total peak area of the relaxation signal is equivalent to the chemically bound water content generated by the sample during the hydration process, as shown in Table 4. It can be seen that the T2 distribution of the sample is mainly in the range of 0.01-10ms. Within 6h, the T2 distribution corresponding to the highest peak of the sample is mainly on the right side of 3ms, C1, C2 and D2 are: 3.29-4.20ms, 3.57-4.94ms and 3.29-4.55ms, respectively, indicating that the water in the cement paste at this stage is mainly free water. At 6h, the signal intensity of the main peak of T2 is C2>C1>D2 from large to small, which is consistent with the data of setting time. At 72h, the T2 corresponding to the highest peak of the sample has shifted to the left to less than 0.28ms. The left shift of the main peak indicates that the main form of water in the sample has undergone a transformation from free water to capillary water and then to gel water. At this time, the water in the sample is mainly capillary water and gel water. This is because as the hydration continues, the hydration products accumulate one by one, and pores gradually form between the particles, thus forming capillary water and gel water. As the hydration proceeds, the peak area of the T2 curve gradually decreases, indicating that the hydration of the sample is gradually progressing. In order to further illustrate the hydration law of the sample, an empirical exponential function fitting is performed in the following text to illustrate it. The data in Table 4 show that at 3d and 28d, the samples are in the order of D2>C2>C1 according to the total peak area reduction value of the T2 curve, indicating that D2 has the largest amount of hydration products, followed by C2, and C1 has the least, which is consistent with the compressive strength data.
[0114] Table 4 Total peak area reduction of T2 curves affected by KH2PO4 and fluorgypsum on hydration of calcium aluminate cement
[0115]
[0116] b. Porosity
[0117] Effects of KH2PO4 and fluorgypsum on the porosity of calcium aluminate cement Fig.11 .Depend on Fig.11 It can be seen that after adding fluorgypsum and KH2PO4 to calcium aluminate cement in sequence, the porosity of the sample tends to decrease. This is mainly because calcium aluminate reacts with fluorgypsum to form ettringite. The addition of KH2PO4 improves the pH environment of the slurry, further increases the amount of ettringite generated, optimizes the hydration products, and thus reduces the porosity. This shows that the addition of fluorgypsum and KH2PO4 promotes the formation of hydration products of calcium aluminate cement, which is beneficial to the development of strength.
[0118] c. Empirical exponential function fitting
[0119] In order to perform quantitative analysis of T2 data (called <t2>), as a function of hydration time. Fig.10 The data were fitted and the fitting function was obtained as shown in formula (7) (refer to RazyqNasharuddin), and the fitting curve is shown in Fig.12 The fitting results are shown in Table 5.
[0120] <t2>=aexp (-bt) +c (7)
[0121] where a is the pre-exponential parameter; b is the decay rate, characterizing the size reduction of the main pore structure of each sample during the hydration process; t is the hydration time; and c corresponds to the necessary value describing the finite (non-zero) pore size exhibited by the sample within the hydration age (28 d).
[0122] As can be seen from Table 5, b2 is in the following order: D2>C2>C1, which indicates that the pore evolution rate among the three gradually slows down, and the rate at which the hydration products enter the pores determines the speed of the pore evolution rate. Therefore, this also indicates that the overall hydration rate is in the following order: D2>C2>C1. Combined with the above-mentioned hydration product generation, which is in the following order: D2>C2>C1, it indicates that the simultaneous addition of 0.2% KH2PO4 and 10% fluorgypsum and the addition of 10% fluorgypsum alone have different degrees of promotion effects on the hydration of calcium aluminate cement.
[0123] Table 5 gives the corresponding parameter reference ranges based on the fitting function.
[0124]
[0125] Effects of KH2PO4 and fluorgypsum on the hydration mechanism of calcium aluminate cement Fig.13 Without adding KH2PO4 and fluorgypsum, the hydration product of calcium aluminate cement is mainly CAH 10 , C2AH8, C3AH6 and AH3. After adding fluorinated gypsum, SO4 2- AFt was generated in its hydration products. At the same time, 10wt% fluorgypsum and 0.2wt% KH2PO4 were added to increase the amount of AFt generated by changing the pH value of the cement slurry, and the morphology of AFt was changed, generating more slender and interlaced fibrous AFt, reducing the porosity of the sample and further improving the compressive strength.
[0126] In summary: Taking calcium aluminate cement paste with a water-cement ratio of 0.40 as the research object, the effects of fluorgypsum and KH2PO4 on the hydration of calcium aluminate cement were compared, and the mechanism analysis was carried out in combination with microscopic tests such as XRD, TG-DTG, SEM and LF-NMR. The main conclusions are as follows:
[0127] (1) Compared with pure calcium aluminate cement (Comparative Example 1), the 3d and 28d strengths of the slurry after adding 10wt% fluorgypsum (Comparative Example 2) were 24.1MPa and 46.5MPa, respectively, which were increased by 60.67% and 152.72% compared with the slurry without addition. This is mainly because fluorgypsum promotes the formation of AFt. As the dosage of KH2PO4 increases from 0% to 0.4%, the setting time first shortens and then prolongs, among which the setting time is the shortest at 0.2wt% dosage (Example 2), which are 264min and 308min respectively; at 0.2% dosage, the 3d and 28d strengths are also the highest, which are 26.4MPa and 60.5MPa respectively, which are 76% and 228.80% higher than those of pure aluminate cement (Comparative Example 1), and 10% and 30.12% higher than those of single-doped fluorinated gypsum (Comparative Example 2). This is mainly because the addition of KH2PO4 improves the pH environment of the slurry, making the AFt morphology become more slender fibers, which are staggered and overlapped with each other, which is beneficial to the compressive strength.
[0128] (2) XRD, TG-DTG and SEM analysis showed that the addition of fluorgypsum promoted the formation of AFt, while the addition of 0.2wt% KH2PO4 (Example 2) increased the amount of AFt generated on the basis of fluorgypsum and changed the morphology of AFt. LF-NMR analysis showed that KH2PO4 and fluorgypsum accelerated the pore evolution rate and promoted the hydration of calcium aluminate cement. When 0.2wt% KH2PO4 and 10wt% fluorgypsum were added simultaneously (Example 2), the porosity of the slurry was the smallest, followed by the addition of 10wt% fluorgypsum alone (Comparative Example 2), and the porosity of the pure calcium aluminate cement slurry (Comparative Example 1) was the largest.
[0129] (3) The addition of fluorgypsum and KH2PO4 improves the hydration of calcium aluminate cement paste and increases its compressive strength. However, the addition of KH2PO4 not only increases the amount of AFt generated, but also changes its morphology into a long and thin fiber, which is easier to overlap each other, further optimizing its pore structure and increasing its compressive strength.
[0130] Application Example 2
[0131] The modified aluminate cement obtained in Example 2 of the present invention and the unmodified aluminate cement obtained in Comparative Example 1 were used to prepare grouting materials, and relevant performance measurements were performed, as follows:
[0132] On the basis of Comparative Example 1 and Example 2, 0.5% of the mass of the modified aluminate cement in Example 2 or the unmodified aluminate cement in Comparative Example 1 was added with a naphthalene-based water reducer to prepare the grouting material. The results show that the initial setting time of the grouting material prepared by Comparative Example 1 is 389 minutes, the final setting time is 463 minutes, and the compressive strengths at 3d and 28d are 15.8 MPa and 19.6 MPa, respectively; the initial setting time of the grouting material prepared by Example 2 is 253 minutes, the final setting time is 285 minutes, and the compressive strengths at 3d and 28d are 25.9 MPa and 61.3 MPa, respectively.
[0133] It can be seen that the modified aluminate cement obtained by the present invention has the advantages of shorter setting time and higher compressive strength than the grouting material prepared by single aluminate cement.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified aluminate cement, characterized in that: The raw material composition includes 90% aluminate cement and 10% fluorgypsum by mass, and 0.1%-0.3% KH2PO4 by mass of the total mass of the above raw materials; The aluminate cement is calcium aluminate cement.
2. The modified aluminate cement according to claim 1, characterized in that Calculated by mass percentage, the raw material composition includes 90% aluminate cement and 10% fluorspar gypsum, and 0.2% KH2PO4 of the total mass of the above raw materials.
3. The modified aluminate cement according to claim 1, characterized in that Calculated by mass percentage, the chemical composition of the calcium aluminate cement includes: Na2O 0-1%, MgO 0-2%, Al2O3 50-60%, SiO2 5-8%, CaO 25-35%, Fe2O3 2-4% and other 0-4%.
4. The modified aluminate cement according to claim 1, characterized in that The main particle size of the calcium aluminate cement: D 10 2-10μm, D 50 35-55μm, D 90 100-200μm.
5. The modified aluminate cement according to claim 1, characterized in that The chemical composition of the fluorgypsum includes, by mass percentage, SO3 55-58%, CaO 40-42.5%, Al2O3 0-0.5%, SiO2 0-0.5%, MgO 0-0.05%, Fe2O3 0-0.5%, K2O 0-0.05%, F-0-1.5% and others 0-0.2%.
6. The modified aluminate cement according to claim 1, characterized in that The main particle size of the fluorgypsum: D 10 0-2μm, D 50 2-5μm, D 90 30-100μm.
7. The modified aluminate cement according to claim 1, characterized in that The KH2PO4 is analytically pure.
8. The method for preparing the modified aluminate cement according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh aluminate cement, fluorgypsum, and KH2PO4 according to the raw material ratio and set aside; (2) Mix aluminate cement, fluorgypsum and KH2PO4, and stir at a speed of 120-160 r / min for 120-180 s to obtain.
9. Use of the modified aluminate cement as described in any one of claims 1 to 7 in grouting materials.
Citation Information
Patent Citations
Modified aluminate cement and preparation method thereof
CN112209642A